Comparison of Cocaine/Crack Biomarkers Concentrations in Oral Fluid, Urine and Plasma Simultaneously Collected From Drug Users. Issue 2 (13th November 2017) - Fiorentin, Taís Regina; Scherer, Juliana Nichterwitz; Marcelo, Marcelo Caetano Alexandre; Sousa, Tanara Rosângela Vieira; Pechansky, Flavio; Ferrão, Marco Flôres; Limberger, Renata Pereira
Abstract: The use of oral fluid (OF) as an alternative specimen for drug analysis has become very popular in forensic toxicology. Many clinical studies have evaluated the correlations between concentrations of cocaine and its metabolites in OF and other matrices, but results have shown high variability. In addition, there are no data available regarding the correlations between biomarkers of crack-cocaine use in different matrices. This study evaluated the relationship between concentrations of cocaine/crack-cocaine biomarkers in OF, urine and plasma samples collected from cocaine users. All samples were analyzed for the presence of cocaine (COC), benzoylecgonine (BZE) and anhydroecgonine (AEC) by a validated liquid chromatography–mass spectrometry method. Median COC, BZE and AEC concentrations ranged from 4.20 to 33.26 ng/mL, from 13.03 to 3, 615.86 ng/mL and from 7.40 to 1, 892.5 ng/mL across matrices, respectively. The relationship between drug concentrations in OF versus plasma (OF/P) and OF versus urine (OF/U) was evaluated by their coefficients of determination ( R 2 ). Least-squares regression analyses demonstrated significant correlations between OF/P and OF/U for cocaine and BE ( P < 0.05), with R 2 = 0.17, 0.07 for cocaine and R 2 = 0.73, 0.45 for BE, respectively. The correlation coefficients (r) found for BZE, COC and AEC in OF/P and OF/U were 0.85 and 0.67 ( P < 0.05); 0.41 and 0.26 ( P < 0.05); and 0.30 and −0.37 ( P > 0.05), respectively. Many factors contribute to the variability of drug correlation ratios in studies involving random samples, including uncertainty about the time of last administration and dosage. Overall, we found significant R 2 values for COC and BZE in OF/P and OF/U, but not for AEC. Despite the good correlations found in some cases, especially for BZE, the large variation in drug concentrations seen in this work suggests that OF concentrations should not be used to estimate concentrations of COC, BZE or AEC in plasma and/or urine.